Arabian nights: a selection - Burton, Richard (Penguin Classics London, 2013)
Probably one of the original 'story within a story' books, Arabian nights is a selection of stories told by a young girl on her wedding night to a prince who has sworn to kill any girl who marries him. Her clever stories serve as 'cliff-hangers' and keep him from murdering her night after night. This collection is where classic fairy tales such as Aladdin and Ali Baba and the Forty Theives come from as well as well-known moral tales and metaphors.The use of djiins, magic and an evocation of Oriental splendour makes Arabian Nights dazzle. A 'must read' book and the perfect counter point to western fairy tales such as Hans Christian Anderson and the Brothers Grimm.